Accrual earning management and future performance: Evidence from family firm in Indonesia - Edy Suprianto; Doddy Setiawan (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2020)
The purpose reasearch is to examine the effect of earnings management on future performance. We also will assess whether auditor have important role in family firms. The population is all companies listed on the Indonesian stock exchanges from 2012 to 2014 (financial industry was excluded). The total sample used in this study as many as 918 firm-years or observations. Model by Kaznik (1999) model was used as an earning management proxy because it better than the other models. We suggest that the average value of the firms family future performance (CFOt+1 and NIt+1) is greater than non-family firms. We also show that accrual earnings management in Indonesia is more efficiency than opportunistic. Accrual earning management which conducted by Family Firms is more efficient than Non-Family Firms. Finally, auditor in family firms will increase future performance.